Transformative Curriculum Development Strategy (Case Study At MTsN 1 Malang City) - Zaini , Mohammad (CV. Inara, 2024)
The purpose of this research is to identify transformative curriculum development strategies at MTsN 1 Malang City. The research method employed is a qualitative research approach. Data collection procedures used in this study include: participant observation, in-depth interviews, and documentation. As this research utilizes a case study design, data analysis is conducted in three stages: (1) data reduction, (2) data display, and (3) verification and conclusion drawing. The research findings include: First, formulating the goals of transformative-integrative curriculum development using the institution's vision and mission. Second, establishing the foundation for transformative-integrative curriculum development, based on the Quran, Hadith, Ijma’, and Qiyas as the specific foundations, and philosophical and juridical foundations as the general basis. Third, determining the principles of transformative-integrative curriculum development, with the main principles being relevance, efficiency, effectiveness, and continuity. Fourth, defining the content of the transformative-integrative curriculum by integrating it with other curriculum such as the National curriculum, pesantren, Cambridge, and specific school curriculum to result in a transformative-integrative curriculum. Fifth, developing a transformative learning schedule; in scheduling, principles of collaboration, fairness, truth, equal distribution, and learning are applied. Sixth, realizing the transformative-integrative curriculum by implementing the PAI curriculum referring to the 2013 Curriculum, NU principles, Javanese language, Tahfidz, learning programs, and the development of students' talents, interests, and skills through extracurricular activities, entrepreneurial education, and habituation programs becoming the cultural norms in the school. Seventh, developing future-oriented learning methods. Eighth, using engaging learning media appropriate to the teaching material. Nineth, establishing collaborations with the community and stakeholders that benefit the institution. Tenth, continuously evaluating the transformative-integrative curriculum, covering three aspects: Learning Evaluation, which includes cognitive, affective, and psychomotor domains; Curriculum Evaluation, which includes components of objectives, content, methods, facilities, and learning evaluation; and Student Achievement Evaluation, which includes academic and non-academic achievements in various competitions.